Associations of Habitual Dietary Intake With Fecal Short-Chain Fatty Acids and Bowel Functions in Irritable Bowel Syndrome. Issue 3 (12th March 2022) - Calderon, Gerardo; Patel, Chirag; Camilleri, Michael; James-Stevenson, Toyia; Bohm, Matthew; Siwiec, Robert; Rogers, Nicholas; Wo, John; Lockett, Carolyn; Gupta, Anita; Xu, Huiping; Shin, Andrea
Abstract : Background & Goals: Diet may contribute to symptoms of irritable bowel syndrome (IBS) and luminal production of putative IBS biomarkers including short-chain fatty acids (SCFAs). Study aims were to to assess relationships of habitual fiber or starch intake with fecal SCFAs in patients with IBS and healthy volunteers (HVs). Study: In 18 HVs and 30 patients with IBS (13 constipation-predominant [IBS-C] and 17 diarrhea-predominant [IBS-D]), habitual diet using a food frequency questionnaire; bowel functions using a validated bowel diary; and fecal SCFAs by HPLC-mass spectrometry were assessed. Associations of fiber and starch with SCFAs were analyzed using Spearman ( r s ) and Pearson ( R ) correlations. Relationships between other dietary endpoints, SCFAs, and bowel functions were explored. Results: Habitual fiber or starch intakes were not significantly correlated with SCFAs or bowel functions in all participants or HVs nor with SCFAs in IBS. Starch was negatively correlated ( R =−0.53; P =0.04) with complete evacuation in IBS-D. Fiber ( r s =0.65; P =0.02) and starch ( r s =0.56; P =0.05) were correlated with ease of passage in IBS-C. Stool form, frequency, and ease of passage were positively correlated with total SCFAs (all P <0.05), acetate (all P <0.01), propionate (all P <0.05), and butyrate (form P =0.01; ease of passage P =0.05) among all participants, but not in IBS. Complete evacuation was negatively correlated with propionate ( R =−0.34; P =0.04) in all participants. Total ( P =0.04) and individual SCFAs (all P <0.05) were positively correlated with stool form in HVs. Conclusions: Habitual fiber and starch intake does not influence fecal SCFAs but may influence bowel functions in IBS. Fecal SCFAs correlate with bowel functions among all participants including HVs.